Carrier detection in X linked ocular albinism using linked DNA polymorphisms. - Charles, S J (1994)
Sixty two females at 50% carrier risk were assessed from 19 families affected by X linked ocular albinism (OA1). Twenty nine (47%) had definite fundus changes of the carrier state with a mud splattered fundus appearance and 23 (37%) had a normal ophthalmic examination. Ten (16%) had mild peripheral retinal pigmentary changes so that it was difficult to exclude the carrier state; six of these females were shown to be at low risk and only one at high risk of being a carrier by DNA analysis using linked DNA polymorphisms, including a highly informative dinucleotide repeat at the Kallmann locus. Mild peripheral retinal pigmentary changes are not a definite indication of carrier status and in 45 age matched female controls five (11%) had similar changes. No female with a clinically normal fundus was found to be at high risk by DNA analysis. Molecular genetic analysis improves the accuracy of carrier detection in OA1 families and should be considered if the clinical findings are equivocal.